1995
DOI: 10.1172/jci118365
|View full text |Cite
|
Sign up to set email alerts
|

A genetic model for absent chylomicron formation: mice producing apolipoprotein B in the liver, but not in the intestine.

Abstract: The formation of chylomicrons by the intestine is important for the absorption of dietary fats and fat-soluble vitamins (e.g., retinol, a-tocopherol). Apo B plays an essential structural role in the formation of chylomicrons in the intestine as well as the VLDL in the liver. We have developed genetically modified mice that express apo B in the liver but not in the intestine. By electron microscopy, the enterocytes of these mice lacked nascent chylomicrons in the endoplasmic reticulum and Golgi apparatus. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
114
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 46 publications
7
114
1
Order By: Relevance
“…Consequently, Apob 100/100 mice excrete a significantly greater amount of fecal neutral steroids than wild-type and Apob 48/48 mice, and increased excretion of these steroids may reduce cholesterol accumulation in the body. 31 Moreover, in an experiment with a small number of mice, Young et al 14 found that disruption of the APO-B gene significantly inhibits cholesterol absorption in mice that express a human APO-B transgene in the liver but do not synthesize any APO-B in the intestine. Therefore, our findings support the concept that APO-B48 is essential for the pack- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, Apob 100/100 mice excrete a significantly greater amount of fecal neutral steroids than wild-type and Apob 48/48 mice, and increased excretion of these steroids may reduce cholesterol accumulation in the body. 31 Moreover, in an experiment with a small number of mice, Young et al 14 found that disruption of the APO-B gene significantly inhibits cholesterol absorption in mice that express a human APO-B transgene in the liver but do not synthesize any APO-B in the intestine. Therefore, our findings support the concept that APO-B48 is essential for the pack- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13 APO-B48 is principally produced by the intestine and is essential for the packaging of alimentary lipids into chylomicrons. 14,15 After intestinal chylomicrons enter the circulation via the thoracic duct, their triglyceride cores are hydrolyzed by lipoprotein lipase and hepatic lipase. The resulting chylomicron remnants, which are enriched with dietary cholesterol, are efficiently and rapidly cleared from plasma by hepatocytes with a half-life of less than 10 minutes.…”
mentioning
confidence: 99%
“…Accordingly, these mice are unable to form chylomicrons or ef®ciently absorb dietary fat; the result is that CHO represents a high percent of absorbed nutrients. Despite the marked reduction of dietary fat absorption (estimated to be 10 ± 20% of normal, based on serum concentrations of lipid-soluble vitamins), these animals maintain normal plasma concentration of triglycerides and cholesterol and are able to accumulate body fat, though at a much lower rate than in normal mice (Young et al, 1995). These observations suggested that DNL might occur at a very high rate, to maintain hepatic lipoprotein secretion and adipose fat deposition.…”
Section: Unanswered Questions Concerning the Regulation And Functionsmentioning
confidence: 98%
“…Young et al have developed a mouse with the endogenous apoB gene knocked out and a human apoB transgene expressed in liver only (Young et al, 1995). Accordingly, these mice are unable to form chylomicrons or ef®ciently absorb dietary fat; the result is that CHO represents a high percent of absorbed nutrients.…”
Section: Unanswered Questions Concerning the Regulation And Functionsmentioning
confidence: 99%
“…Genetically altered mice have been reported that lack various apoproteins or lipoprotein receptors, that are deficient in canalicular lipid transporters, that are defective in the promoters that regulate bile acid synthesis, and that have deletions of one of the major pathways for the formation of acidic sterols. [30][31][32][33][34][35][36] These models offer powerful tools for understanding the molecular mechanisms of cellular sterol balance. Unfortunately, however, there exist very few published data describing the comparative features of bile acid metabolism and its regulation in this species.…”
mentioning
confidence: 99%